Kerja Sehat: Aplikasi Mobile Untuk Mengurangi Resiko Musculoskeletal Disorders (MSDs) - Fikky Aprico; Muhammad Syakir Arif; Dihin Muriyatmoko; Azis Musthafa; Ario Ramadhan; Sisca Mayang Phuspa; Ratih Andhika Akbar Rahma (Ikatan Ahli Informatika Indonesia (IAII), 2019)
Musculoskeletal Disorders (MSDs) are complaints in the skeletal muscles caused by behavioral errors and work attitudes. If the condition happens every day for long, it can cause permanent pain and damage to muscles, joints, tendons, ligaments and othes. The Occupational Safety and Health Administration (OSHA) recommends ergonomic measures to deal with complaints of MSDs under the Ergonomic Rule of Twenty (ERT) rules. The purpose of this study is applying the method to android application. Work on this application using the steps of waterfall. Testing is done in 5 ways. The first with the blackbox method indicates that the application is running smoothly with no error. The second hardware use with various smartphones and screen size shows that the application is running well on minimum specification 4.3-inch and Android KitKat operating system. The third was carried out to two MSDs expert lecturers indicating that the application was in accordance with the ERT rules and recommended to be used as a media to prevent MSDs complaints. Fourth, by distributing questionnaires to 32 educational staff respondents at University of Darussalam Gontor, actively sitting in front of the computer daily, give good feedback with a score of 82%. Fifth, through users (https://play.google.com/store/apps/details?id=id.amoled.timerapp), 10 users gives rating of 4.6 from March 27 to July 20, 2019. All results show this application complies with ERT rules and helps prevent and reduce complaints of MSDs. This Application is recommended for anyone having a job with the habit of sitting in front of a computer for long time.